Management of concomitant umbilical hernia with laparoscopic cholecystectomy - Singhal, Vinod K.; Aswad, Faris D. Al; Diddi, Gaurav; Singhal, Vidher V. V.; Suleiman, Adil M. (International Surgery Journal, 2023)
Background: During laparoscopic cholecystectomy (LC) procedures, umbilical abnormalities may present technical challenges for general surgeons and increase the risk of incisional hernia. Objective was to identify the best repair technique to go along with LC for known or incidentally discovered umbilical hernias. Methods: In this study, retrospective review of the medical records of patients who had concurrent LC and umbilical hernia repair was done. Between January 2020 and January 2023, our institution performed LC on 600 patients, 65 (10.5%) of whom also underwent simultaneous UHR and LC. The analysis included 65 (10.5%) patients who met the inclusion requirements. Patients with umbilical hernias were identified during the preoperative phase by a clinical examination. Results: Mean age of 65 qualifying patients who underwent LC+UHR was 54.7±14.9 years (range 23-81 years) Men and women comprised 41 (65.6%) and 24 (34.4%) of these 65 patients, respectively. Median VAS pain scores measured on the first, second and seventh days were higher in group 3 compared with those of the other two groups. There were statistically significant differences between different days in groups 1, 2 and 3 (p=0.01). Conclusions: The outcomes of the UHR with mesh after laparoscopic surgeries appear to be better for either obese or non-obese patients than primary suture techniques in recurrence rates.